Total Phenolics, Flavonoids, Anthocyanins and Antioxidant Activities of Khaow-Mak Extracts from Various Colored Rice - Wattanuruk, Duangduan; Phasuk, Sasamol; Nilsang, Poonyanuch; Takolpuckdee, Pannraphat (Journal of Food Health and Bioenvironmental Science, 2023)
Khaow-Mak is fermented food of rice, which contains a lot of nutrients and antioxidant bioactive compounds. Generally, Khaow-Mak is fermented from cooked white glutinous rice. However, it can be fermented with colored rice (black, purple and red pericarp colored grains) in order to increase bioactive compounds and antioxidant performance. The study was conducted to investigate the chemical composition of Khaow-Mak extracts, total phenolic, flavonoid and anthocyanin contents. The antioxidant activities were evaluated by using the scavenging towards 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP). The colored rice was collected from 16 local colored rice (red, black and purple) around Thailand. The cooked rice was fermented with a starter (Look Pang) at room temperature for 5 days. Fermented rice samples were extracted with 95% ethanol for 24 hours. Dried crude extracts were obtained using a rotary evaporator at 45°C. The results showed that the content of bioactive compounds of all colored rice were increased after fermenting time. Leum Phua glutinous rice had the highest contents of total phenolic (45.66±0.01 mgGAE/g) flavonoid contents (39.35±0.07 mgRE/g) and anthocyanin contents (3.37 ± 0.21 mg/g). In addition, Leum Phua glutinous rice showed the hightest antioxidant activity of DPPH (EC50 0.364±0.02 mg/ml) and FRAP (28.018±0.01 mgFe(II)/g. These results potentially support the use of local rice extracts as the active raw material of functional food and/or cosmetics.